Addressing substance use and vulnerability among unaccompanied migrant youth in Spain: A narrative review - Mc-Gragh, Bosko; López Atanes, Mayte; Rico, Rocio; Bari, Melav; Millin, Sascha; Behrendt, Malte; Schäfer, Ingo; Erkoreka, Leire (Addicta: The Turkish Journal on Addictions, 2026)
Spain’s geographic position has made it a key entry point for forced migrants, including unaccompanied minors (UMs), from regions such as North Africa and the Middle East. These minors often face pre-migration trauma and post-migration stressors—including social isolation, economic hardship, and administrative insecurity—significantly increasing their risk of mental health disorders and substance use as a maladaptive coping mechanism. Given the specific focus on youth in migration contexts, this narrative review evaluated existing psychosocial and treatment interventions for forced migrants with substance use disorders in Spain. The analysis of available literature reveals significant regional disparities in protection systems for UMs, exacerbating vulnerabilities such as emotional distress and migratory grief, while substance use was consistently identified as a symptom of deeper systemic and psychological issues rather than a primary disorder. A key finding was the notable absence of specific intervention models for this population. In light of this gap, a community-based participatory action research (CBPAR) model emerged as a promising, though yet to be adapted, framework for developing culturally sensitive interventions that could address structural drivers of risk. The review concludes that effective intervention requires a dual approach: policy reforms to standardize equitable, trauma-informed care across regions, and investment in the development and implementation of participatory, community-driven programs prioritizing holistic healing and integration. It also underscores the urgent need for a paradigm shift toward culturally competent, empowerment-focused strategies in Spain and to inform international responses to the complex needs of forced migrant youth.
Keywords: unaccompanied minors; substance use disorders; mental health; migration trauma; health equity; Spain